Effect of Methanolic and Phenolic Extracts of Nigella sativa Seeds on Testicular Expression Levels of inhibin alpha and beta Genes in Mature Male Wistar Rats - Jabbar Jasim Hamady, Kamal Gahzi Ganim, Zainab Sattar Ali (Journal of Applied Pharmaceutical Science, 2016)
To examine the effect of crude methanolic extract and phenolic compounds obtained from Nigella sativa seeds on testicular expression levels of inhibin-α, -βA, and –βB subunits of intact mature male rats, thirty males were randomly assigned to three equal groups (C, M, and P). Males were orally administered with distal water, methanolic extract of N. sativa seed at the dose of 1.0 g/ kg b.w., and phenolic extract of N. sativa seed at the dose of 0.3 g/ kg b. w., daily for 18 days. At the end of treatment period, male rats were anesthetized by single injection of thiopental (100 mg/ kg, i.p.), sacrificed, and testes were removed. Samples from testicular tissues were quickly dipped in DEPC solution and frozen at -80 ºC until gene expression levels assessment of inhibin subunits by using semi-quantitative RT-PCR analyses. Male rats that have been treated with phenolic compounds (P group) registered marked increase of all inhibin subunits compared with those treated with methanolic extract, which they were also higher than that of control males. It can be concluded that phenolic compounds of N. sativa seeds have the more efficient role in reproductive functions than methanolic extract of N. sativa seed.
Keywords: Inhibin, Nigella sativa, fertility, testis.